Mapping The Trajectory Of Succession Planning In Family Based Companies- A Critical Analysis - Chatterjee, Nilavro; Banerjee, Dr. Shivaji (The journal of contemporary issues in business and government, 2021)
Family businesses are the germination locus of all enterprise universally, they contribute a sizeable quantum of funds to their national exchequer throughout the free world globally. Their size and gamut are from micro corner shops to large conglomerates like TATA Empire, Ford, Samsung et al are globally known and recognized. The promoters are invariably ambitious, having sharp business acumen and profound compatibility with the environment and competition, the challenge emerges when through efflux of time the original group has to make way and successors to step in to their shoes, this is more so when there are multiple claimants and all of them might not have the caliber or inclination. The plausible solution to this enigma is the topic of this treatise with case studies, some succession are still ongoing process like Cyrus Mistry versus Tata and Lodha versus Birla, some has lost relevance like nationalization of IISCO a hangover of an old arcane concept. The new concept of family counsel as prevailing in Dabur and gradual professional ethos in Tata are interesting, if carefully juxtaposed avoiding mélange might yield appropriate solutions if not panacea albeit keeping within the realm of the Indian Corporate Law, ethos and Taxation laws.